THE IMPORTANCE OF ORAL PERFORMANCE: WHAT MAKES A SUCCESSFUL PROFICIENCY-BASED FOREIGN LANGUAGE PROGRAM - Peter Suwarno (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
Major Foreign Language (FL) programs in Indonesia, i.e. Indonesian for non-native speakers (BIPA) and English for Indonesian Speakers (EIS), have no standard of assessments on what constitutes a successful program. Some in-country BIPA programs that measure their success using Oral Proficiency Interviews (OPI) show the standard of success in the form of oral proficiency. This paper’s purpose is to argue that oral proficiency tests such as OPI is not only a good measure of learners’ communicative competence in general, but it also necessitates curriculums, methods, and activities geared toward the better level of communicative proficiency. Therefore, FL learning should emphasize oral proficiency to show a higher level of performable learning outcomes. Based on class observations as well as interviews of BIPA and EIS learners and instructors, this paper shows that lack of oral performance practices and assessments lead to achievement in the target language (TL) knowledge but not the communicative competence. Thus, if communicative competence is the goal, oral proficiency must be the main outcome of any FL programs.